The child code : understanding your child's unique nature for happier, more effective parenting - Dick, Danielle M. (Danielle Marie) (Avery, an imprint of Penguin Random House, 2021)
"A provocative, science-based approach to parenting centered on a child's unique genetic 'code,' from an award-winning developmental psychology professor and researcher"--